Linking ASI-Mobile Android-Based App on Mothers Attitude and Behavior on Exclusive Breastfeed (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Exclusive breastfeeding within the Palangka Raya municipality is far below target, on which 14,99% (2016) and 16,76% (2017), respectively. There were several primary health has the feeding bout, only cover 2,58%. Due to a lack of mothers knowledge, regarding beneficial and proper breastfeeding practices. Todays technology presumably has the advantages as promotional media. The study was aimed to quantify the android-based application, so-called ASI-Mobile, towards mothers attitude and behavior, on exclusive breastfeeding within Jekan Raya district, Palangka Raya Municipality, Central Kalimantan. The Research was conducted in March - October 2019, using a quasi-experimental design, and the sample was 60 pregnant women, in the third trimester period, over the Jekan Raya District areas. ASI-Mobile was subjected to 30 pregnant women, while others 30 mothers by counseling, the conventional promotion type. Purposive sampling was used, their socio-economic was collected, descriptive analysis was conducted. Bivariate analysis, Wilcoxon ranked test was used to analyzed the effect of the treatments. We've have found a significant link on ASI-Mobile application toward mothers attitudes (p-value 0.046) and behavior (p-value 0.018). We concluded that the ASI-Mobile, an android-base application, is more effective towards shifting mothers attitudes and behavior on exclusive breastfeeding within our study area.